Pricing and Hedging American Options: A Recursive Integration Method - Huang, Jing-zhi; Subrahmanyam, Marti G.; Yu, G. George (Review of Financial Studies, 1996)
In this article, we present a new method for pricing and hedging American options along with an efficient implementation procedure. The proposed method is efficient and accurate in computing both option values and various option hedge parameters. We demonstrate the computational accuracy and efficiency of this numerical procedure in relation to other competing approaches. We also suggest how the method can be applied to the case of any American option for which a closed-form solution exists for the corresponding European option. Article published by Oxford University Press on behalf of the Society for Financial Studies in its journal, The Review of Financial Studies.